Optimization of Bookkeeping and Transaction Recording Systems to Improve Financial Quality in Sogga Batik UMKM - Rosita Rahayu; Audita Nuvriasari (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The internship at Sogga Batik aims to help optimize the bookkeeping and transaction recording system to improve the quality of business finances. Sogga Batik, located in Krebet Tourism Village RT 04, Sendangsari, Pajangan, Bantul, Yogyakarta Special Region, is an MSME that produces and markets cloth batik, wood batik, and ecoprint. However, the financial management of this business still faces several obstacles, such as the absence of standardized recording guidelines, financial records that are not in accordance with standards and the lack of use of digital technology. Through this internship program, students contribute by developing SOPs for financial records, providing training based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) and assisting in the implementation of a digital financial recording system. The internship also includes the development of promotional media such as product catalogs to improve marketing. The results of this program are expected to have a positive impact on Sogga Batik, including recording efficiency, improving the accuracy of financial statements, and expanding market reach through better promotion. This activity not only improves students' ability in theory application, but also supports the development of local culture-based MSMEs as an effort to preserve traditional heritage.